Real-World Challenges of Using Assisted Living Technologies across Different Australian Aged Care Settings: A Qualitative Study of User Experiences - Afzal, Nida; Nguyen, Amy D.; Lau, Annie (Applied Clinical Informatics, 2025)
Aging populations strain health care systems. Assisted Living Technologies (ALTs) emerge as a potential solution for promoting independent living among older adults. However, the real-world effect of ALTs remains unclear.This study explores benefits and challenges (anticipated and unanticipated) of ALTs for older adults and informal caregivers across three aged care settings (residential aged care facilities [RACFs], retirement villages [RVs], and home-dwelling communities [HDCs]) in Australia.Three ALTs (fall detection sensors, sleep monitors, and smartwatches) were deployed across three settings. NASSS framework (Non-adoption, Abandonment, Scale-up, Spread, and Sustainability), informed by sociotechnical theories, guided analysis of the interplay between technology, user needs, and caregiving context in ALTs implementation. Semistructured interviews with 14 older adults and 9 caregivers from 19 households explored user experiences. Benefits and challenges of using ALTs for older adults and informal caregivers were categorized using the consequences framework.Setting-specific challenges alongside common benefits and challenges across care settings were revealed. The NASSS framework analysis showed how technology limitations, user needs, and caregiving context influenced these outcomes. In RACFs, where residents receive constant nursing assistance, informal caregivers faced uncertainty regarding who was responsible for monitoring residents. In RVs, with a strong sense of community, informal caregivers (often neighbors) were more prone to overreacting to false alarms. Shared sleeping arrangements among HDCs made interpreting sleep data challenging.Implementing ALTs in elderly care settings requires a context-sensitive approach. In RACFs, clear role definitions for informal caregivers and staff are essential. For RVs, design should support help-seeking aligned with residents' social and geographical contexts. Home-dwelling settings may benefit from advanced sleep monitoring tailored to shared living arrangements. Future ALTs development should focus on real-world contexts to promote successful aging in place.
Keywords: ambient assistive technologies; older adults; caregivers; aging in place; qualitative